2021
DOI: 10.1186/s13567-020-00882-x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of regulated cell death in the lung of piglets infected with virulent PRRSV-1 Lena strain occurs earlier and mediated by cleaved Caspase-8

Abstract: PRRSV-1 virulent strains cause high fever, marked respiratory disease and severe lesions in lung and lymphoid organs. Regulated cell death (RCD), such as apoptosis, necroptosis and pyroptosis, is triggered by the host to interrupt viral replication eliminating infected cells, however, although it seems to play a central role in the immunopathogenesis of PRRSV, there are significant gaps regarding their sequence and activation upon PRRSV-infection. The present study evaluated RCD events by means of caspases exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 74 publications
(121 reference statements)
2
14
0
Order By: Relevance
“…GO terms such as “cytokine-mediated signaling pathway,” “response to bacterium,” “regulation of cytokine production,” “IFN-I signaling pathway,” and “cellular response to tumor necrosis factor” were enriched in this cluster. According to our previous results and those from others, these inflammatory-related pathways contribute to the severe clinical outcomes and lung lesions observed in Lena-infected piglets, but also to an early upregulation of pro-inflammatory cytokines associated with a high viral load and the induction of regulated cell death ( 14 , 39 42 ). These results confirm that the dynamics and extent of virulent Lena strain replication are critical for the disease outcome, inducing a strong and early inflammatory response in the lung.…”
Section: Discussionsupporting
confidence: 60%
“…GO terms such as “cytokine-mediated signaling pathway,” “response to bacterium,” “regulation of cytokine production,” “IFN-I signaling pathway,” and “cellular response to tumor necrosis factor” were enriched in this cluster. According to our previous results and those from others, these inflammatory-related pathways contribute to the severe clinical outcomes and lung lesions observed in Lena-infected piglets, but also to an early upregulation of pro-inflammatory cytokines associated with a high viral load and the induction of regulated cell death ( 14 , 39 42 ). These results confirm that the dynamics and extent of virulent Lena strain replication are critical for the disease outcome, inducing a strong and early inflammatory response in the lung.…”
Section: Discussionsupporting
confidence: 60%
“…Curiously, in our study, a peak of the FASL gene was demonstrated in the lung and tracheobronchial lymph node from virulent Lena-infected piglets parallel to the expression of EOMES , which was also shown through immunohistochemical expression of Fas. The interaction of Fas/FasL mediates the cleavage of caspase-8, a mediator of extrinsic apoptotic pathway ( 65 ), whose activation has been previously described in the lung and thymus from animals infected with the virulent Lena strain ( 20 , 21 ). Moreover, EOMES, together with T-bet, could also be co-expressed in naïve and effector CD8 + T cells, which promotes IFN-γ, perforin, and granzyme B expressions ( 3 , 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the Th1 and effector CD8 phenotypes by the upregulation of the T-bet gene is also supported in our study by the overexpression of the cytokine TNFA in the tracheobronchial lymph node and lung of virulent Lena-infected animals at the end of the study. This pro-inflammatory cytokine has been associated with apoptosis and other cell death phenomena in the context of PRRSV infection, specifically during infection with the virulent Lena strain, not only in the lung but also in the thymus ( 20 , 21 ), helping to explain the severity of the lesions associated with this strain. Whereas IFN-γ + and TNF-α + cells were mainly located in lymphocytes from the medullar area in the tracheobronchial lymph node and thymus, pointing out lymphoid lineage (expressing the T-bet gene) as the major source of IFN-γ and TNF-α in these organs, the expressions of these cytokines in the lung were mostly evidenced in interstitial and pulmonary alveolar macrophages, mainly associated with local inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods—widely used in human and veterinary pathology—allow the examination of the histopathological changes and to observe the amount, the distribution, as well as the cell tropism of the given pathogen within the tissues. These features can be useful to assess the pathological role of PRRSV in natural cases of porcine respiratory disease complex [ 32 ], but the methods are more commonly used in experimental settings, where PRRSV is the only pathogen [ 33 ].…”
Section: Discussionmentioning
confidence: 99%